2020
DOI: 10.3102/0162373720922218
|View full text |Cite
|
Sign up to set email alerts
|

School Closures in Chicago: What Happened to the Teachers?

Abstract: In 2013, the Chicago Board of Education closed 47 elementary schools, directly affecting 13,000 students and 900 teachers. The closures created employment uncertainty for closed-school teachers, and this article investigates the labor market consequences for teachers. We employ a difference-in-differences approach that compares the exit rates of closed-school teachers with teachers in schools that only experienced threat of closure. We estimate that the closures resulted in a near doubling of teacher exit amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although all schools faced initial threat of closure, the Chicago Board of Education voted to close 47 elementary schools. Lee and Sartain (2020) find that teachers in closed schools were more likely to leave the school district compared to teachers in under-enrolled and lowperforming schools that faced initial threat of closure and teachers in schools that were never at risk.…”
Section: The Effects Of Sanctions and Rewards Embedded In School Acco...mentioning
confidence: 77%
“…Although all schools faced initial threat of closure, the Chicago Board of Education voted to close 47 elementary schools. Lee and Sartain (2020) find that teachers in closed schools were more likely to leave the school district compared to teachers in under-enrolled and lowperforming schools that faced initial threat of closure and teachers in schools that were never at risk.…”
Section: The Effects Of Sanctions and Rewards Embedded In School Acco...mentioning
confidence: 77%
“…Further research could explore why and how those shifts occur and how teacher networks respond to uncertainties within the labor market. Research shows that Black teachers are more often affected by firings due to school closures and the instability of district restructuring that often precipitates those closures (Cook & Dixson, 2013; Lee & Sartain, 2020; Lincove et al, 2018; White, 2018). Hiring decisions, and unequal access to job opportunities among teacher candidates, in part due to the reliance on networks, created conditions where teachers who can cultivate a stronger network, or with access to the “right” networks, had greater opportunities for employment.…”
Section: Discussionmentioning
confidence: 99%
“…Cook and Dixson (2013) reported that Black teachers decreased by 71%, shrinking from 2,759 teachers in the 2004-2005 school year to 801 in 2006-2007. Similar kinds of workforce restructuring occurred in other large, urban cities (e.g., New York, Newark, Philadelphia, Washington DC, and Chicago) where teachers were fired in mass and/or were subjected to school turnaround initiatives, systems of punitive accountability, choice, and competition (Lee and Sartain 2020;Lipman 2013aLipman , 2013bWhite 2016). School closures, in particular, also disproportionately affect Latinx and Black students and teachers.…”
Section: Historical and Contemporary Trends Of Employment Insecurity ...mentioning
confidence: 92%
“…Indeed, there is mounting evidence illustrating that Black teachers in the U.S. experience hyper-precarity as they are continuously subjected to discriminatory hiring and firing practices, involuntary demotions and transfers, workplace hostility, contract nonrenewal, and work displacement (Carter Andrews et al 2019; D’amico et al 2017; Kohli 2018; Lee and Sartain 2020; White 2016). Given their complex racial/ethnic histories, intersectional identities, and social location, ToC experience the work and job of teaching differently than white teachers.…”
Section: Introductionmentioning
confidence: 99%